Successful Robotics Practices in Integrated Secondary Education: Teaching of the knowledge learned in a training course in Porto-PT (Research, Society and Development, 2022)
In the contemporary educational context, movements driven by technological development and its relevance and appropriation by Teaching are emerging, among them is Robotics, introduced and defended by Seymour Papert as one of the ways to promote learning, being an innovative model in the educational context, an active methodology. On the other hand, it is known that the Brazilian public school faces several challenges, either in the promotion of the permanent education of its teachers, or in the necessary infrastructure to allow the inclusion of subsidized educational practices in Digital Technologies of Education. Without refraining from these challenges, this article presents and discusses a successful practice of applying the knowledge learned in a training course in Porto-PT, highlighting Educational Robotics in a Public Institution of Federal Education for Comprehensive High School Students, using the Active STEAM Methodology and, as pedagogical resources for learning robotics, the Arduino UNO Kit, the Tinkercad simulator, the Lego Mindstorms Kit and the Mbot2 robot.